Development of perennial thaw zones in boreal hillslopes enhances potential mobilization of permafrost carbon - Walvoord, Michelle A; Voss, Clifford I; Ebel, Brian A; Minsley, Burke J (Environmental research letters, 2019)
Permafrost thaw alters subsurface flow in boreal regions that in turn influences the magnitude, seasonality, and chemical composition of streamflow. Prediction of these changes is challenged by incomplete knowledge of timing, flowpath depth, and amount of groundwater discharge to streams in response to thaw. One important phenomenon that may affect flow and transport through boreal hillslopes is development of lateral perennial thaw zones (PTZs), the existence of which is here supported by geophysical observations and cryohydrogeologic modeling. Model results link thaw to enhanced and seasonally-extended baseflow, which have implications for mobilization of soluble constituents. Results demonstrate the sensitivity of PTZ development to organic layer thickness and near-surface factors that mediate heat exchange at the atmosphere/ground-surface interface. Study findings suggest that PTZs serve as a detectable precursor to accelerated permafrost degradation. This study provides important contextual insight on a fundamental thermo-hydrologic process that can enhance terrestrial-to-aquatic transfer of permafrost carbon, nitrogen, and mercury previously sequestered in thawing watersheds.